UJI BATANG BAWAH KARET (Hevea brassiliensis, Muell-Arg.) BERASAL DARI BENIH YANG TELAH MENDAPAT PERLAKUAN PEG (SEED COATING) DENGAN BEBERAPA KLON ENTRES TERHADAP KEBERHASILAN OKULASI - Melinsani Manalu; Charoq Charoq; Asil Barus (Jurnal Agroekoteknologi, 2014)
For increasing rubber production, seed factor very important as rootstock origin. Seed haverecalsitran characteristic that cause the deteoration. The seed that have gotten the PEG treatment tomaintain the viability, tested further as rootstock origin. The purpose of this study was to test therootstock of the rubber (Hevea brassiliensis, Muell-Arg.) originated by the seeds that have gottenthe PEG treatment with some clones of Scion for the success of grafting the research have done onMarch until June, 2013 in the publics land at Pasar I Tanjung Sari, Medan. The design of researchthat be used is Randomize Complete Factorial Design with two factors and three replications. Thefirst factor is rootstock seed of rubber that has been gotten the seed treatment (0%, 15%, 30%, 45%PEG concentrate) and the second factor is scion (IRR 104, IRR39, IRR 72 clones). The parameterthat be observed is break bud in field, the length of bud and the diameter of bud. The result showedthat the rubber rootstock seed that have given the seed treatment did not effected significantly on allof parameters. The type of scion did not effected significantly on all of parameters. The interactionsbetween rootstock and the scion did not effected significantly also. On all of the parameters the bestresult that gained on the rootstock of rubber seed that have given by the seed treatment is theconcentrate of PEG 30% and bud of IRR 104.Keywords: Rootstock of rubberseed, Scion clones, grafting.